Romania: a case study in delayed privatization - McCollum, James K.; Schoening, Niles C. (2002)
Romania emerged from 45 years of communism with 12,000 enterprises in state hands. As the nation moved toward democracy and free market conditions, its new leaders created legislation to privatize at least half of the state owned enterprises. In the years 1990 to 1996, the actions to privatize state owned enterprises went slowly, even though outside organizations such as the International Monetary Fund, World Bank, and European Union urged speed in privatization. Until November 1996, former communists who had high positions under Nicolae Ceasusescu led the government. After 1996, with a reform coalition running the country, privatization speeded up and made a difference in the country's economy. Privatization continues even though the government changed hands again in 2000. Romania's delayed privatization program has so far precluded the emergence of a new group of powerful owners who become so strong they can stymie the long-term achievement of a fully reformed economy. - Reproduced.
Keywords: Privatization